2016
DOI: 10.1039/c6ra05581h
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy formation and migration in double perovskite Sr2CrMoO6: a first-principles study

Abstract: These calculations provided theoretical insight into the effect of the B-site Cr and Mo on the oxygen vacancy formation and migration in the double perovskite Sr2CrMoO6 using the DFT+U method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…To reveal the effect of Br-vacancy on the electronic property of Cs 2 AgBiBr 6 , we calculated the density of states (DOS) for pure and Br-vacancy Cs 2 AgBiBr 6 surface using the method of GGA-PBE. From Figure 8 , it can be deduced that the forming of Br-vacancy can move the Fermi level from VBM to near the CBM, which is consistent with previous work on studying the O-vacancy and Cl-vacancy [ 80 , 81 , 82 ]. As the peak introduced by defective states is sharp and separated from the relatively delocalized electrons in the conduction band, the exceeding electrons brought by vacancy are localized.…”
Section: Resultssupporting
confidence: 88%
“…To reveal the effect of Br-vacancy on the electronic property of Cs 2 AgBiBr 6 , we calculated the density of states (DOS) for pure and Br-vacancy Cs 2 AgBiBr 6 surface using the method of GGA-PBE. From Figure 8 , it can be deduced that the forming of Br-vacancy can move the Fermi level from VBM to near the CBM, which is consistent with previous work on studying the O-vacancy and Cl-vacancy [ 80 , 81 , 82 ]. As the peak introduced by defective states is sharp and separated from the relatively delocalized electrons in the conduction band, the exceeding electrons brought by vacancy are localized.…”
Section: Resultssupporting
confidence: 88%
“…The O 1s core level spectra are fitted corresponding to three types of oxygen peaks, lattice oxygen, chemisorbed oxygen, and physisorbed oxygen. From Figure (c), it was observed that the intensity signal of chemisorbed oxygen is stronger than that of lattice oxygen. The presence of chemisorbed oxygen at the surface could be attributed to defect correlation with dopant concentration and lattice oxygen associated to the formation of oxygen vacancies. , Zhao et al reported that oxygen vacancy formation and migration in double perovskite can be useful as an anode for SOFCs. The calculated percentage factors of lattice oxygen and chemisorbed oxygen given in Table indicate that the amount of chemisorbed oxygen is increased with a decrease in lattice oxygen.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The presence of chemisorbed oxygen at the surface could be attributed to defect correlation with dopant concentration and lattice oxygen associated to the formation of oxygen vacancies. 44,45 Zhao et al 46 reported that oxygen vacancy formation and migration in double perovskite can be useful as an anode for SOFCs. The calculated percentage factors of lattice oxygen and chemisorbed oxygen given in Table 2 indicate that the amount of chemisorbed oxygen is increased with a decrease in lattice oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Cr 3+ creates the positively charged oxygen vacancies (V •• O ). The ionic radii of Cr 3+ and Mo 5+ valence states are identical, so there is a high probability of producing antisite defects, which are electron and oxygen vacancies (V •• O ) [27]. According to the Anderson model, the antisite defects in double perovskites might be generated due to octahedral disorder caused by the charge difference of B site cations (two or more).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported [27] that the bond between Cr-O is different from the Mo-O due to electron transfer between Cr cation and O ion, which is bridged by strong ionic bonds. SCM is an interesting material due to its potential applications in spintronics and magneto-transport devices [25,28].…”
Section: Introductionmentioning
confidence: 99%